The structure of the human CD2 gene and its expression in transgenic mice. - Lang, G (1988)
We report the genomic organization of the human CD2 gene and its expression in transgenic mice. A 28.5 kb segment of DNA consisting of 4.5 kb 5' flanking sequences, 15 kb containing the gene's five exons and 9 kb of 3' flanking sequences can direct the expression of the CD2 gene only on thymocytes, circulating T cells and megakaryocytes of the transgenic mice. The expression of each copy of the human CD2 transgene appears to be as high as the endogenous mouse CD2 gene and as high as the expression on the surface of human T lymphocytes, independent of the site of integration and dependent on the copy number of genes that have integrated.